Displacement & Domesticity Since 1945: Refugees, Migrants and Expats Making Homes, Following the EAHN’s Sixth Thematic Conference (Brussels, 27–28 March 2019) - Ashika L. Singh; Alessandra Gola; Luce Beeckmans; Hilde Heynen (Architectural Histories, 2020)
In the recent history of globalisation and mass human displacement, the practical and epistemological tools of architecture play a role in revealing the multi-faceted relationship between migration and home. The goal of the European Architectural History Network’s sixth thematic conference was to illuminate and critically reflect on the conceptual role and socio-material expressions of domesticity employed in response to displacement in contemporary history, beginning with the year 1945. Many of the papers reflected a deep interest in the processes involved in thinking, building and preserving home as well as the growing importance of interdisciplinary and cross-cultural collaborations. Inspired by this, we seek to prompt ways, especially from within the architectural discipline and community, to conceive of alternative epistemological and heuristic frameworks for integrating interdisciplinary knowledge.